We have matrix: A=
Find the eigenvalues of the matrix:
Associate matrix Vlasna vectors values and introduce a variable.
"\\begin{pmatrix}\n 2- \\lambda & 1 & 2 \\\\\n 1 & 3-\\lambda & 1 \\\\\n 2 & 2 & -6 - \\lambda\n\n\\end{pmatrix}"
To do this, find the determinant of the matrix and equate this expression to zero.
"(2-\\lambda)*((3 - \\lambda)*(-6-\\lambda)-2*1)-1*(1*(-6=\\lambda)-2*2)+2*(1*1-(3-\\lambda)*2)=0"
After transformations, we get:
"\\lambda"3"+\\lambda"2 "-31\\lambda +40 = 0"
After applying the rules, it is clear that the roots of the equation are not integers. Let's calculate the approximate "\\lambda" .
"\\lambda"1 "=-6,60"
"\\lambda"2 "=4,15"
"\\lambda"3 "=1,45"
Multiply the matrix A by the matrix of its eigenvalues:
"\\begin{pmatrix}\n 2 & 1 & 2 \\\\\n 1 & 3 & 1 \\\\\n 2 & 2 & -6\n\\end{pmatrix}" "*" "\\begin{pmatrix}\n -6,6 \\\\\n 4,15 \\\\\n 1,45\n\\end{pmatrix}" "=" "\\begin{pmatrix}\n -6,15 \\\\\n 7,3 \\\\\n -13,6\n\\end{pmatrix}"
Maybe, if I misunderstood something, I add to the report: the sum and product of the matrix A itself:
The sum of the matrix: A + A = 2A
"2\\begin{pmatrix}\n 2 & 1 & 2\\\\\n 1 & 3 & 1\\\\\n2 & 2 & -6\n\\end{pmatrix}=\\begin{pmatrix}\n 4 & 2 & 4 \\\\\n 2 & 6 & 2\\\\\n4 & 4 & -12 \n\\end{pmatrix}"
And product of the matrix: "A * A = A^2"
"A*A=\\begin{pmatrix}\n 2 & 1 & 2 \\\\\n 1 & 3 & 1 \\\\\n2 & 2 & -6\n\\end{pmatrix}*\\begin{pmatrix}\n 2 & 1 & 2 \\\\\n 1 & 3 & 1 \\\\\n2 & 2 & -6\n\\end{pmatrix}=\\begin{pmatrix}\n 9 & 9 & -7 \\\\\n 7 & 12 & -1 \\\\\n-6 & -4 & 42\n\\end{pmatrix}"
Multiplication is performed for each component of the matrix separately:
"a^2_11=a_11*a_11 +a_12*a_21+a_13*a_31= 2*2+1*1+2*2=9"
"a^2_12=a_11*a_12 +a_12*a_22+a_13*a_32=2*1+1*3+2*2=2+3+4=9"
"a^2_13=a_11*a_13 +a_12*a_23+a_13*a_33= 2*2+1*1+2*(-6)=-7"
"a^2_21=a_21*a_11 +a_22*a_21+a_23*a_31=1*2+3*1+1*2=7"
"a^2_22=a_21*a_12 +a_22*a_22+a_23*a_32=1*1+3*3+1*2=12"
"a^2_23=a_21*a_13 +a_22*a_23+a_23*a_33=1*2+3*1+1*(-6)=-1"
"a^2_31=a_31*a_11 +a_32*a_21+a_33*a_31= 2 *2 +2*1+(-6)*2=-6"
"a^2_32=a_31*a_12 +a_32*a_22+a_33*a_32=2*1+2*3+(-6)*2=-4"
"a^2_33=a_31*a_13 +a_32*a_23+a_33*a_33=2*2+2*1+(-6)*(-6)=42"
Comments
Leave a comment